Conjact Glucomannan Flour Extraction From Porang Tube (Amorphophallus muelleri Blume) with Differents Simplicia- Solvent Ratio (Subject were obtained from the Klagon Village of Saradan District): Ekstraksi Tepung Konyak Glukomanan dari Umbi Porang (Amorphophallus muelleri Blume) pada Berbagai Perbandingan Simplisia-Pelarut (sampel didapatkan dari desa Klangon Kabupaten Saradan) - Kusumo, Galuh Gondo (Akademi Farmasi Surabaya, 2021)
This study aimed to determine the best simplicia-solvent comparison to extract Konyak Glucomannan (KGM) flour from porang tubers (Amorphophallus muelleri Blume) that obtained from Klangon Village, Saradan District. Extraction was carried out by water solvent with solvent-simplicia comparison of 1: 100; 1: 200; 1: 300; 1,5: 100; 1,5: 200; and 1,5: 300. The extraction was carried out at a temperature of 45oC and 55oC for 60 minutes. The results showed that the extraction of Konjac Glucomannan (CGM) flour, was optimally extracted with a 1: 300 simplicia-solvent ratio at 55oC for 60 minutes.